’Oumuamua: A Mysterious Visitor From Deep Space - Khalil, M.; Said, M.; Osman, H.; Younis, N.; Khaled, N.; Amr, Y.; A. Mohamed, Nour; Ibrahim, A. (International Journal of Advanced Astronomy, 2021)
The mysterious visitor 'Oumuamua is the first interstellar object ever seen in our solar system. It was discovered by the Pan-STARRS tele-scope on 19 October 2017. A short overview of 'Oumuamua is presented in this paper. Moreover, we present this work to spotlight on the fact that, there are trillions of such interstellar objects that could visit our solar system.Â Â